Teaching Photonics - Rutkowska, Katarzyna Agnieszka; Karpierz, Mirosław (Photonics Letters of Poland, 2017)
There is a need to teach modern photonics as a tool for technology of the 21st century. Apart from the studies in Applied Physics, Faculty of Physics at the Warsaw University of Technology (WUT) offers a program in English which leads to the M.Sc. degree in Photonics. The two-year graduate program in the area of Photonics provides students a unique opportunity to become familiar with the applications of light in fields that range from fundamental research to technological applications. The aim of this Master?s Program is to form engineers and scientists with solid basic knowledge in the field of photonics and with the skills to apply this knowledge to the design, realization and the management of photonic systems for a broad range of application domains.